Design for Manufacturing and Assembly Optimization of Home-Scale Biodigester-Composter Using VDI 2222 and Finite Element Analysis Methods - Wijaya, Dewa Kusuma; Suprijono, Herwin; Santoso, Heru Agus; Kusmiyati, Kusmiyati; Muchti, Muhammad Agusdika Ridho (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
This research focused on the Design for Manufacturing and Assembly (DFMA) optimization of home-scale biodigester-composter machines. The aims to determine feasibility from technical-economic aspects. The technique was to design the machine's mechanical process, physical, and constituent components. There are two methods conducted on this research, VDI 2222 to optimize and Finite Element Analysis (FEA) to assess the optimal quality results of the machine design based on simulation analysis. This research ended with making a physical prototype of a home-scale biodigester-composter machine using the optimal design, then validating it with a working test of the machine. The results of the VDI 2222 method show an optimal design concept through the structure of the working mechanism. All its constituent components match with the ten target specifications and the machine manufacturing cost of IDR 2,393,000, as well as the assembly chart design for each constituent component. These results are also evaluated using the FEA method. The resistance value of the frame system to maximum Von Mises Stress is obtained at 128.75 MPa with a minimum value of 6.93e-04 MPa. It is concluded to be acceptable at withstanding normal and shear stresses effectively with a relatively small displacement value of 0 to 0.47 mm. The equivalent strain value results are 3.89e-09 ul to 5.83e-04 ul and safety factor value results are 1.93 to 15 ul. It can be concluded that the frame system design concept is safe.